Implementation of Validity and Reliability Tests on Service Satisfaction Levels of the Spotify Application Using SPSS Software - Resmi Hayati, Kinanti; Setiyoningsih, Titi; Izzah, Navisatul; Islamey, Tarisa A; Yuanda, Tiara A (UPN Veteran Jatim, 2024)
Spotify is a legal digital music application widely used for online streaming, especially popular among students. This popularity provides a solid foundation for conducting a case study on user satisfaction levels with Spotify in Indonesia. The research employs a questionnaire to collect data, which is subsequently tested for validity and reliability using SPSS software. The results indicate that several variables, such as improved user experience, user-friendly interface, useful features, and fast performance, have high validity values, with significance levels below 0.05. These variables exceed the r-table, with values ranging from 0.5 to 0.904. In cases where any variable is found invalid, retesting will be conducted to ensure the data is valid. Reliability testing produced a Cronbach's alpha coefficient of 0.772, demonstrating that the data used in this study is reliable, as it exceeds the acceptable threshold of 0.6. Therefore, this research provides valuable insights into user satisfaction levels regarding Spotify's services in Indonesia, making it a trustworthy resource for understanding user experiences and areas for improvement within the application. Overall, the findings contribute to a deeper understanding of user preferences and satisfaction in the digital music streaming landscape.